Pengaruh Penggunaan Artificial Intelligence (AI) dan Kemandirian Belajar terhadap Kreativitas Mahasiswa Program Studi Pendidikan Bisnis Stambuk 2022 Fakultas Ekonomi Universitas Negeri Medan - Julia Retni Ainaya; Lenti Susanna Saragih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the effect of the use of artificial intelligence (AI) and independent learning on the creativity of students of the 2022 Business Education Study Program, Faculty of Economics, State University of Medan. This study uses a quantitative method with an expo-facto approach. The sample in this study amounted to 63 respondents selected using the total sampling technique. The data collection technique was carried out through the distribution of questionnaires and creativity tests, while the data analysis technique used multiple linear analysis. The results of the study indicate that the use of artificial intelligence (AI) and independent learning simultaneously have an effect on the creativity of students of the 2022 Business Education Study Program, Faculty of Economics, State University of Medan. Based on these results, it is recommended that students can use technology wisely while continuing to develop independent learning skills to support optimal creativity.